2019
DOI: 10.1080/19420862.2019.1685349
|View full text |Cite
|
Sign up to set email alerts
|

In vivo safety profile of a CSPG4-directed IgE antibody in an immunocompetent rat model

Abstract: IgE monoclonal antibodies hold great potential for cancer therapy. Preclinical in vivo systems, particularly those in which the antibody recognizes the host species target antigen and binds to cognate Fc receptors, are often the closest approximation to human exposure and represent a key challenge for evaluating the safety of antibody-based therapies. We sought to develop an immunocompetent rat system to assess the safety of a rodent anti-tumor IgE, as a surrogate for the human therapeutic candidate. We genera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 62 publications
3
21
0
Order By: Relevance
“…Furthermore, tumour antigens released into the blood as monomers are not expected to induce crosslinking of FceR-bound IgE required for degranulation 44 . Consistently, no signs of anaphylaxis were found in preclinical models and safety data was satisfactory in both rodents and monkeys 44,47,48 .…”
Section: Use Of Alternative Ig Isotypes: Igesupporting
confidence: 55%
“…Furthermore, tumour antigens released into the blood as monomers are not expected to induce crosslinking of FceR-bound IgE required for degranulation 44 . Consistently, no signs of anaphylaxis were found in preclinical models and safety data was satisfactory in both rodents and monkeys 44,47,48 .…”
Section: Use Of Alternative Ig Isotypes: Igesupporting
confidence: 55%
“…We confirmed target antigen recognition by the antibody and its ability to be internalized by antigen-expressing tumor cells using a reporter assay. Previous studies have shown that CSPG4-expressing tumors could be targeted with CSPG4-specific agents [38][39][40][41]. This included the monoclonal antibody Ep1 to deliver cisplatin encapsulated in protein cages [42].…”
Section: Discussionmentioning
confidence: 99%
“…Although tumour antigens released into the blood as monomers are not expected to induce cross‐linking of FcɛR‐bound IgE required for degranulation [54], circulating tumour cells expressing multiple copies of targeted antigen would have the potential to induce degranulation. However, no signs of anaphylaxis were found in preclinical models and safety data were satisfactory in both rodents and monkeys [54,57,58], supporting the initiation of the first clinical trial using a tumour‐targeting anti‐folate receptor alpha IgE mAb MOv18 (NCT02546921). Interim Phase I data from 24 patients support the safety and potential efficacy of MOv18 IgE [59].…”
Section: Tumour Antigen‐targeting Mabsmentioning
confidence: 98%